THE NATIONAL AND INTERNATIONAL WATER POLICIES WITH FOCUS ON THE DRAINAGE WATER REUSE PRACTICES AND THE MEGA WATER PROJECTS - Khairy, Wael M. (International Journal of Research -GRANTHAALAYAH, 2022)
The overgrowing water scarcity in Egypt should be the motive to develop alternative water resources. The article focuses on a technical review of the state-of-the-art water policies for the reuse of agricultural drainage water in irrigation worldwide and in Egypt, due to the increasing pace of implementing mega water projects. Satisfying future water demands in Egypt depends on better utilization and efficient use of the available water resources. Optimal water management, particularly the nonconventional water resources, is an essential prerequisite for the sustainable development of Egypt. The hypotheses examined are that the available quantities of agricultural drainage water in Egypt shall decrease and the quality of that drainage water shall improve. In the meantime, it is expected that soil and water salinity rates shall rise as a result of the multiple reuses of the drainage water and also due to the expansion of modern irrigation practice not only in the newly reclaimed desert lands but also in some old heavy soil lands. In addition, a technical review of the impacts of those changes above on the phenomenon of seawater intrusion in the northern parts of the Nile Delta is presented. It is concluded that the impact of the national water-saving, irrigation improvement projects, and expansion in land reclamation in the desert are inversely proportional to the resulting amount of agricultural drainage water in Egypt. That reduction is interpreted as about 20%, which needs further extensive applied research to verify. That amount might be compensated with the safe reuse of treated wastewater, with the due health safeguards. Accordingly, as stated in the NWRP2037, caution should be taken while projecting the future available agricultural drainage water for reuse in each geographic zone in Egypt.